2018
DOI: 10.1038/s41598-018-35086-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Non-coding RNAome of RPE cells under oxidative stress suggests unknown regulative aspects of Retinitis pigmentosa etiopathogenesis

Abstract: The discovery of thousands of non-coding RNAs has revolutionized molecular biology, being implicated in several biological processes and diseases. To clarify oxidative stress role on Retinitis pigmentosa, a very heterogeneous and inherited ocular disorder group characterized by progressive retinal degeneration, we realized a comparative transcriptome analysis of human retinal pigment epithelium cells, comparing two groups, one treated with oxLDL and one untreated, in four time points (1 h, 2 h, 4 h, 6 h). Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 103 publications
2
11
0
Order By: Relevance
“…If oxidized, they may impair transduction pathways and gene expression [19]. Although fatty acid oxidation was already confirmed to cause macular degeneration, oxidative stress mechanism in RP development requires further clarifications [20]. Therefore, to better understand how high ROS levels may lead to retinal dystrophies onset and progression, we performed a comparison of transcriptomes' profiles among human RPE cells exposed to the oxidant agent N-retinylidene-N-retinylethanolamine (A2E).…”
Section: Introductionmentioning
confidence: 99%
“…If oxidized, they may impair transduction pathways and gene expression [19]. Although fatty acid oxidation was already confirmed to cause macular degeneration, oxidative stress mechanism in RP development requires further clarifications [20]. Therefore, to better understand how high ROS levels may lead to retinal dystrophies onset and progression, we performed a comparison of transcriptomes' profiles among human RPE cells exposed to the oxidant agent N-retinylidene-N-retinylethanolamine (A2E).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA expression evaluation of oxidative stress-induced retinal pigment epithelium cells has shown a regulative role of miRNA in retinitis pigmentosa that should lead to the discovery of new ways to influence the etiopathogenesis of this disease [14]. Moreover, a decrease in the activity of detected piRNAs could be explained by the inhibition of silencing activity of miRNA regulation of the DNA damage response and transporter activity of retinal pigment epithelium cells in oxidative stress [15].…”
Section: Introductionmentioning
confidence: 99%
“…FEELnc, an alignment-free program that accurately annotates lncRNAs based on a random forest model trained with general features, and BLASTX (McGinnis and Madden, 2004) were used to identify and classify lncRNAs in this study. FEELnc (Wucher et al, 2017) has been shown to achieve similar or better classification performance on GENCODE (Harrow et al, 2012) and NONCODE (Bu et al, 2011) data sets when compared with five programs [PhyloCSF (Lin et al, 2011), CPC (Kong et al, 2007), CPAT (Wang et al, 2013), PLEK (Li et al, 2014), and CNCI (Sun et al, 2013)], and has previously been used to identify lncRNAs (Che et al, 2018; Donato et al, 2018; Wang et al, 2018). In this study, 2,623 novel lncRNAs were identified, of which 1,484 were classified.…”
Section: Discussionmentioning
confidence: 99%